PENGARUH PENGGUNAAN MEDIA POSTER INTERAKTIF TERHADAP KEAKTRIFAN BELAJAR PESERTA DIDIK PADA MATA PELAJARAN IPAS DI KELAS V SD NEGERI 8 METRO UTARA - Tia, Destia; Nur Asiah; Muhammad Muchin Afriyadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the problem of low learning activeness of students in IPAS subjects in Class V SD Negeri 8 Metro Utara, which encourages researchers to apply Interactive Poster Media. The purpose of this study is to determine the effect of using interactive poster media on student learning activeness in IPAS subjects in class V SD Negeri 8 Metro Utara. This study uses a quantitative approach with a quasi-experimental research design. This research was conducted at SD Negeri 8 Metro Utara, specifically in class V, involving two classes as experimental and controlgroups, andone additional class as a validation class. The research instrument used was a questionnaire to collect data, which was then analyzed with prerequisite tests and hypothesis testing using the t-test. The results showed that the normality test produced a value of 0.200 and 0.200, which means >0.05,indicatingthatthedataisnormallydistributed.Thehomogeneitytestshowed a value of 0.219 > 0.05, indicating that the data is homogeneous. The results of the hypothesis test using the Independent Sample T-Test produced a value of 0.003 < 0.05, which means H0 is rejected and H1 is accepted, so it can be concluded that there is a significant effect on student learning activeness in IPAS subjects in Class V SD Negeri 8 Metro Utara.This research is motivated by the problem of low learning activeness of students in IPAS subjects in Class V SD Negeri 8 Metro Utara, which encourages researchers to apply Interactive Poster Media. The purpose of this study is to determine the effect of using interactive poster media on student learning activeness in IPAS subjects in class V SD Negeri 8 Metro Utara. This study uses a quantitative approach with a quasi-experimental research design. This research was conducted at SD Negeri 8 Metro Utara, specifically in class V, involving two classes as experimental and controlgroups, andone additional class as a validation class. The research instrument used was a questionnaire to collect data, which was then analyzed with prerequisite tests and hypothesis testing using the t-test. The results showed that the normality test produced a value of 0.200 and 0.200, which means >0.05,indicatingthatthedataisnormallydistributed.Thehomogeneitytestshowed a value of 0.219 > 0.05, indicating that the data is homogeneous. The results of the hypothesis test using the Independent Sample T-Test produced a value of 0.003 < 0.05, which means H0 is rejected and H1 is accepted, so it can be concluded that there is a significant effect on student learning activeness in IPAS subjects in Class V SD Negeri 8 Metro Utara.